Development of a miniature digital data processing 4πβ(LS)-γ(LaBr3) coincidence system at KRISS. (November 2022) - Han, Minji; Hwang, S.H.; Agusbudiman, Agung; Kim, B.C.; Lee, J.M.; Lee, K.B.; Heo, D.H.
Abstract: A miniature 4π β (LS)– γ (LaBr3 ) coincidence system for the activity measurement of beta-gamma-emitting nuclei was developed using digital data processing at the Korea Research Institute of Standards and Science (KRISS). The system was configured with two photomultiplier tubes for beta measurements, and two LaBr3 gamma detectors. A pilot experiment was conducted using a 60 Co source. The highest beta-detection efficiency achieved with 60 Co was found to be 93.7%. The activity concentration with the new system was found to be (5665 ± 27) kBq ( k  = 2). This value is in agreement with the reference ionization chamber at KRISS within the uncertainty of the new system. Highlights: Development of a miniature 4π β (LS)- γ (LaBr3 ) coincidence system. A digital data acquisition (DAQ) with a coincidence trigger logic with internal FPGA. A primary measurement has been performed with a 60 Co source. The measured activity is compared with the reference ionization chamber.